Lichens of Akerman medieval fortress (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
Lichens of 44 species are found from the territory of Akkerman medieval fortress, with prevailing majority (31 species) of epilitic taxa. It is shown that the maximal amount of species grows in microecotopes of moist and shaded fortress moat walls. Among the found species Physconia muscigena is new for the steppe zone of Ukraine.
Keywords: lichens, biodegradation, fortress, microecotopes.